(untitled) (Revista de Ciências Agroveterinárias, 2024)
Aedes aegypti is the primary vector of viruses that cause diseases such as dengue, yellow fever, Zika, and Chikungunya, leading to high rates of morbidity and mortality in humans and substantial healthcare costs. The most common method for mosquito control involves the use of synthetic insecticides; however, continuous use of these substances leads to species resistance and environmental contamination. In response to these challenges, natural extracts have emerged as a promising alternative for vector control as they contain components potentially toxic to mosquitoes. The aim of this review is to present the current state of the use of natural extracts as a strategy for controlling both larval and adult Ae. aegypti. By means of information retrieval from databases, considering original articles published from 2018 to 2023, we sought information related to the plant part used for extract obtainment, extraction methods, and solvents used. A total of 676 articles were found, of which 35 met the established criteria. In these publications, 38 families, 69 genera, and 87 species of plants were identified, with a particular emphasis on the Asteraceae, Anacardiaceae, Myrtaceae, and Lamiaceae families due to their higher number of species used in research. On the other hand, the most commonly used methods for obtaining extracts included maceration with subsequent filtration, as well as Soxhlet extraction. Meanwhile, the preferred solvents for extract obtainment were ethanol and water. In conclusion, there is widespread use of plant extracts as insecticides, with extraordinary potential to control vector populations such as Ae. aegypti and, in turn, contribute to the reduction of arbovirus transmission by this mosquito.